Polyclonal spread of multiple genotypes ofMycoplasma pneumoniaein semi‐closed settings in Yamagata, Japan. Issue 5 (May 2019) - Suzuki, Yu; Seto, Junji; Shimotai, Yoshitaka; Itagaki, Tsutomu; Katsushima, Yuriko; Katsushima, Fumio; Ikeda, Tatsuya; Mizuta, Katsumi; Hongo, Seiji; Matsuzaki, Yoko
Abstract : N/A: Purpose. To clarify the spread of Mycoplasma pneumoniae infections in semi‐closed settings such as schools and family homes using molecular typing methods. Methodology. We retrospectively searched for school‐ and family‐based clusters of M. pneumoniae infections based on information regarding patients from whom M. pneumoniae strains had been isolated between 2011 and 2013 in Yamagata, Japan. The molecular typing profile, including the P1 type and the four‐locus (Mpn13, 14, 15 and 16) multiple‐locus variable‐number tandem‐repeat (VNTR) analysis (MLVA) type, was obtained from our previous study. Results. We identified 11 school‐based clusters involving 71 patients and 16 family‐based clusters involving 38 patients, including 14 duplications between these types of clusters. A total of 95 M. pneumoniae strains isolated from those patients were divided into 4 genotypes: 33 strains of type 4‐5‐7‐2, 1; 31 of type 4‐5‐7‐3, 1; 24 of type 3‐5‐6‐2, 2c; and 7 of type 3‐5‐6‐2, 2a. Of the 11 school‐based clusters, 6 clusters (54.5%) consisted of multiple genotypes, and the remaining 5 clusters consisted of a single genotype. Moreover, the presence of multiple genotypes was identified in three classrooms of a school. On the other hand, in 14 (87.5%) of the 16 family‐based clusters, the genotypes of the M. pneumoniae strains isolated from each family member were identical. Conclusion. The spread of M. pneumoniae infection in schools is likely polyclonal, since M. pneumoniae strains are brought into schools from various sites, such as family homes, which are important sites of disease transmission.